The Charité external cephalic version for leading twin breech without regional anesthesia and tocolysis. A prospective study on feasibility, sonographic assessment and outcomes. (January 2022) - Hinkson, Larry; Schauer, Madeleine; Latartara, Elisabetta; Alonso-Espias, Maria; Rossetti, Emma; Gebert, Pimrapat; Hinkson, Susan; Henrich, Wolfgang
Highlights: External cephalic version for twin A breech is feasible. External cephalic version for twin A breech does not require regional anesthetic. External cephalic version for twin A breech does not require tocolysis. External cephalic version or twin A breech reduces the need for cesarean. Abstract: Objectives: To assess the feasibility of external cephalic version (ECV) for the leading twin (twin A) in breech presentation in dichorionic and diamniotic twin pregnancies without the use of regional anesthetics and tocolysis and to characterize the sonographic parameters, maternal and neonatal outcomes. Study design: Prospective study performed in the Charité University Hospital outpatient obstetric department in Berlin, Germany. A total of 23 women from the 35th completed week of pregnancy with confirmed dichorionic-diamniotic twin pregnancy were recruited. ECVs were performed by the lead consultant for the breech and ECV clinic. Ethical approval provided by the Charité Ethics Commission (EA2/241/18). Demographic data were recorded. Fetal sonographic parameters were assessed. The success rate of ECV, duration of the ECV, gestational age at delivery, mode of delivery for both fetuses, maternal and neonatal outcomes were analyzed. Results: Our main finding showed that ECV for twin A breech in dichorionic-diamniotic twins is successful in 56% (10/18) of cases without the need for regional anesthesia and without tocolysis. There is a significant increase in the spontaneous vaginal delivery rate for both twins of 95% (19/20) vs 12.5% (2/16) (p < 0.001). There is also a significant reduction in blood loss at delivery of 300 ml vs 500 ml (p = 0.034) in successful cases. Conclusions: We show that ECV for twin A in breech is feasible and in 56% (10/18) successful without regional anesthesia and tocolysis. The option of ECV for twin A breech should be offered to women.